2007
DOI: 10.2337/db06-0473
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Variations in CCK, Leptin, and Leptin Receptor Genes Are Associated With Specific Human Eating Patterns

Abstract: Obesity has a heritable component; however, the heterogeneity of obesity complicates dissection of its genetic background. In this study, we therefore focused on eating patterns as specific traits within obesity. These traits have a heritable component; genes associated with a specific eating pattern have not yet been reported at the population level. In this study, we determined whether genetic variations in cholecystokinin (CCK) and leptin genes underlie specific eating patterns. We selected obese individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…Although it has been reported that genetic variations underlie specific eating patterns (14) and sweet preference is considered to be a risk factor for obesity, few reports have shown an association between them (15), and none have examined whether human LEP and LEPR polymorphisms have effects on sweet preference. However, there have been several reports indicating associations between LEP/LEPR polymorphisms and obesity (5).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been reported that genetic variations underlie specific eating patterns (14) and sweet preference is considered to be a risk factor for obesity, few reports have shown an association between them (15), and none have examined whether human LEP and LEPR polymorphisms have effects on sweet preference. However, there have been several reports indicating associations between LEP/LEPR polymorphisms and obesity (5).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it may be worthwhile to select on more specific or additional (endo)phenotypic characteristics, such as personality characteristics or measures of eating behaviour. For example, it was shown that cholecystokinin and leptin (receptor) polymorphisms are associated with meal size and snacking frequency (77) , which makes these behavioural measures potential selection criteria for a genotype associated with 'overeating'.…”
Section: Genetic Effectsmentioning
confidence: 99%
“…CCK variants (rs6809785, rs7611677, rs6801844, and rs6791019) were found to be more associated with extreme meal size, but not increased snacking behavior in the same study. This study 13 suggests that genetic variation in genes encoding CCK and leptin may contribute to obesity risk by influencing satiety. However, the research article 27 surprisingly overlooked the earlier research efforts regarding genetic variation to body weight and body shape.…”
mentioning
confidence: 99%
“…CCK is released 35 in response to lipids and promotes rapid post-prandial satiety in contrast to the long term action of leptin. In a large case-control study 13 of obese and normal weight women, common leptin variants, (rs4577902, rs2060736, and rs4731413), have been found to be associated with increased risk of extreme snacking behavior (top 5th percentile based on 11 question questionnaire), but not increased meal size. CCK variants (rs6809785, rs7611677, rs6801844, and rs6791019) were found to be more associated with extreme meal size, but not increased snacking behavior in the same study.…”
mentioning
confidence: 99%
See 1 more Smart Citation